Prevalence of Radiographic Errors in IOPA - Monica Antony1, Dhanraj Ganapathy2, Leelavathi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Radiographs are considered as a crucial aid in diagnosis, intraoral and post operative evaluation of differentconditions and dental procedures. Exposing the patient to beams of x ray more than needed is time consumingand increases treatment cost. Some of the errors include cone cut, overlap, elongation, shortening, hazyimage, ghost image, artifacts and reversed film.The aim of the study is to determine the prevalence ofradiographic errors in IOPA. The study was aimed to investigate the correlation of radiographic errorsin IOPA. 100 case reports of patients were obtained from Dental Archive Software and was tabulated inExcel. The data analysis was done using SPSS software. The graphs were obtained and the results weretabulated. Overlap type of error was more prevalent for upto 41%. There were more errors as well likeelongation 16%, shortening 17%, hazy image 12%, cone cut 13% and ghost image 1%. 27% of the studypopulation that underwent radiographic errors were between 21 to 30 years. 36% of the errors were causedby molars. Undergraduate students performed more errors in which overlap occurred for 26% while amongpostgraduate students they occurred for 15%(figure 5). Overlap type of error was the most common causeof radiographic error. Radiographs being one of the golden standards for diagnosis, need to be done withproper knowledge and awareness.